PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN MEDIASI VARIABEL MOTIVASI PADA PT BINTANG BORNEO METALINDO BANJARMASIN - Septyawan, Sandra; Saddewisasi, Wyati; Santoso, Djoko (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2024)
PT. Bintang Borneo Metalindo Banjarmasin who interact directly with the leadership, it can be concluded that the leadership applies a transformational leadership style. However, the implementation of this leadership style is not optimal. The leadership has not fully utilized the appeal and charisma in inspiring vision and enthusiasm, and is lacking in helping to solve problems, paying attention to the individual needs of employees, and providing training and advice. The leadership's busyness with company affairs makes time to share and provide motivation limited.This research method, the researcher must first decide on the research method to be used. The research method is the approach chosen by the researcher to achieve the research objectives. Based on this, this study uses the census method, which means that the entire population consisting of 67 people is taken as the object of research. To collect the necessary data, this study uses several techniques, namely questionnaires, interviews, and observations.Based on the results of the research that has been done, it can be concluded as follows: Transformational leadership has no significant effect on employee motivation at PT. Bintang Borneo Metalindo Banjarmasin. Work discipline has a significant and positive effect on motivation at PT. Bintang Borneo Metalindo Banjarmasin.Transformational leadership has a significant and positive effect on employee performance at PT. Bintang Borneo Metalindo Banjarmasin.Work discipline has a significant and positive effect on employee performance at PT. Bintang Borneo Metalindo Banjarmasin.Motivation has a significant and positive effect on employee performance at PT. Bintang Borneo Metalindo Banjarmasin.Transformational leadership has an effect on employee performance mediated by motivation at PT. Bintang Borneo Metalindo Banjarmasin.Work discipline has an effect on employee performance mediated by motivation at PT. Bintang Borneo Metalindo Banjarmasin